Sympathetic Enhancement of Memory T-Cell Homing and Hypertension Sensitization. Issue 6 (13th March 2020) - Xiao, Liang; do Carmo, Luciana Simao; Foss, Jason D.; Chen, Wei; Harrison, David G.
Abstract : Rationale: Effector memory T lymphocytes (TEM cells) exacerbate hypertension in response to repeated hypertensive stimuli. These cells reside in the bone marrow for prolonged periods and can be reactivated on reexposure to the hypertensive stimulus. Objective: Because hypertension is associated with increased sympathetic outflow to the bone marrow, we hypothesized that sympathetic nerves regulate accumulation and reactivation of bone marrow–residing hypertension-specific TEM cells. Methods and Results: Using unilateral superior cervical ganglionectomy in wild-type C57BL/6 mice, we showed that sympathetic nerves create a bone marrow environment that supports residence of hypertension-specific CD8 + T cells. These cells, defined by their proliferative response on coculture with dendritic cells from Ang (angiotensin) II–infused mice, were reduced in denervated compared with innervated bone of Ang II–infused mice. Adoptively transferred CD8 + T cells from Ang II–infused mice preferentially homed to innervated compared with denervated bone. In contrast, ovalbumin responsive T cells from OT-I mice did not exhibit this preferential homing. Increasing superior cervical ganglion activity by activating Gq-coupled designer receptor exclusively activated by designer drug augmented CD8 + TEM bone marrow accumulation. Adoptive transfer studies using mice lacking β2AR (β2 adrenergic receptors) indicate that β2AR in the bone marrow niche, rather than T-cell β2AR is critical for TEM cell homing. Inhibition of global sympathetic outflow using Gi-coupled DREADD (designer receptor exclusively activated by designer drug) injected into the rostral ventrolateral medulla or treatment with a β2AR antagonist reduced hypertension-specific CD8 + TEM cells in the bone marrow and reduced the hypertensive response to a subsequent response to low dose Ang II. Conclusions: Sympathetic nerves contribute to the homing and survival of hypertension-specific TEM cells in the bone marrow after they are formed in hypertension. Inhibition of sympathetic nerve activity and β2AR blockade reduces these cells and prevents the blood pressure elevation and renal inflammation on reexposure to hypertension stimuli. Abstract : Supplemental Digital Content is available in the text.